OH-stretch overtone of methanol: empirical assignment using a two temperature technique in a supersonic jet1. Issue 24 (28th June 2015) - Svoboda, Vít; Horká-Zelenková, Veronika; Rakovský, Jozef; Pracna, Petr; Votava, Ondrej
<x xml:space="preserve">Abstract</x> Application of two-temperature analysis in combination with GSCD is demonstrated to provide reliable assignments in methanol high resolution overtone spectra measured in supersonic jet expansion.